MODEL PENGEMBANGAN PERILAKU SEHAT IBU HAMIL SEBAGAI UPAYA MENURUNKAN ANGKA KEMATIAN IBU DI KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Sotyania Wardhianna Wardhianna (Kesmas Indonesia, 2011)
ABSTRACT Till now, realized, that death of momeny mother bear the baby of is a symptom concerning. Knowledg and education concerning healthy pregnant mother still far form enough word. During the time, seems,behavior of mather at the of pregnancy less obey to obey inspection which passimg phasa-inspection step periodical, this matter more and more streghten assumption will the lack of education and knowledge. The research will be in a few phase. First phase,will be done by survey, utilized kuestioner-concerning healthy behavior and kwoledge of pregnant mother distric of Sokaraja. Second phase,conducted Focussed Group Discussion (FGD) With result of FGD will be formed by healthy Kader of Pregnant Mother (KaSIH) what consisi of countryside midwife and mother which have home, what share to medel effective counseling. Obtained result that mother know about pregnancy risk 38,95% and inspection of pregnancy 67% but not conducted periodical,even not be done at the time earlypregnancy ang also not comprehend marking pregnancy oh high risk. After counseling, formed by healthy cadre (Kader) pregnant mother, which during the time there’s only cadre of balita and of lansia. The cadre fuction to be facilitate pregnan mother enquire concerning health of pregnancy and not only reliing on at midwife (Bidan) which have stired because wide of activite region. Key word : Knowledge, education, Cadre. Kesmas indo. Volume 4, Nomor 1, Januari 2011, hlm. 60-71